The Study of Soil Characteristics At Sycamore Rice Planting In Sangir Region, Solok Selatan Regency - Zulkifli, Zulkifli; Hermon, Dedi; Thesiwati, Aslan Sari (Pendidikan Geografi, 2013)
The research was conducted in Sangir region, Solok Selatan regency to see and analyze soil characteristic ( structure, texture, permeability, pH, organik matter ) for plant of sycamore rice in sangir region, solok selatan regency. The method which was used in this research was descriptive that described about object character which was researched, then compared with the administrative mapping unit and land unit. Land unit was got from overlay of several maps that were map of land from unit, slope, land using, soil and geology. The unit land map was become basit of taking the research sample. The sample was got by strativied random sampling tectnique where the sample of research was taken from strata or degree of land unit. The re sult of research showed thad the research area consisted of four land forms, they were1) land form of volcanic umpland (V1), 2) land form of volcanic hill (V2), 3) land form of volcano down slope (V3), 4) land form of volkanoÂ  down (V4). By soil characteristic of land unit which was researched for sycamore rice plant in Sangir region, Solok Selatan regency. Soil characteristics of land unit which were researched for the sycamore rice plant in Sangir region were there was soil characteristic, they were good, medium and bad. At the land unit V1,Toa,I,Sw,Gh and V2 Mpip,II,Sw,Gh, its soil characteristtics were good and land unit are V3 Qvbe,III,Sw,Gh, ist soil characteristic were medium, althouggh in every permabilitas of all the research land unit was categoritedÂ  bad. The degree of soil characteristics at the land of sycamore rice planting in Sangir region were divided into categories, that were good category at the land unit of volcanic plain (V1,Toa,I,Sw,Gh) and land unit of volcanic hill (V2,Mpip,II,Sw,Gh), and medium categories located at the third sample center with the land form unit of volcano down slope (V3,Qvbe,III,Sw,Gh)